PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DI PT INDOLAND BATAM - Tan, Denis; Purba, Daris (LPPM Universitas Putera Batam, 2021)
This research aims to analyze if there is any influence from promotion and product quality towards the customer satisfaction of PT Indoland Batam which engages in the online shop. The phenomenon of fluctuation of the customer satisfaction level for PT Indoland Batam reflects the customer satisfaction has not been maximized. This research uses two independent variables which are promotion variable and product quality variable. The technique used in collecting data used in this research is the distribution of questionnaire using accidental sampling method, whereby the sample used in this research are amounting to 148 respondents. This research uses technical data analysis methods such as validity test, reliability test, classic assumption test, multiple linear regression analysis, determination coefficient test, and hypothesis test. The result of this research show that promotion and product quality variable partially does have positive influence and is significant towards the consumer satisfaction. Furthermore, promotion and product quality variable simultaneously does have positive influence and is significant towards the customer satisfaction of PT Indoland Batam. Variables in this research have an influence od 29,7% towards the performance of employees. The rest 70,3% are influenced by other variables coming from outside of this research.